Goats without Prion Protein Display Enhanced Proinflammatory Pulmonary Signaling and Extracellular Matrix Remodeling upon Systemic Lipopolysaccharide Challenge - Salvesen, Øyvind; Reiten, Malin R.; Kamstra, Jorke H.; Bakkebø, Maren K.; Espenes, Arild; Tranulis, Michael A.; Ersdal, Cecilie (Frontiers in Immunology, 2017)
A naturally occurring mutation in the PRNP gene of Norwegian dairy goats terminates synthesis of the cellular prion protein (PrPC), rendering homozygous goats (PRNPTer/Ter) devoid of the protein. Although PrPC has been extensively studied, particularly in the central nervous system, the biological role of PrPC remains incompletely understood. Here, we examined whether loss of PrPC affects the initial stage of LPS-induced acute lung injury. Acute pulmonary inflammation was induced by intravenous injection of LPS (Escherichia coli O26:B6) in 16 goats (8 PRNPTer/Ter and 8 PRNP+/+). A control group of 10 goats (5 PRNPTer/Ter and 5 PRNP+/+) received sterile saline. Systemic LPS challenge induced sepsis-like clinical signs including tachypnea and respiratory distress. Microscopic examination of lungs revealed multifocal areas with alveolar hemorrhages, edema, neutrophil infiltration, and higher numbers of alveolar macrophages, with no significant differences between PRNP genotypes. A total of 432 (PRNP+/+) and 596 (PRNPTer/Ter) genes were differentially expressed compared with the saline control of the matching genotype. When assigned to gene ontology categories, biological processes involved in remodeling of the extracellular matrix (ECM), were exclusively enriched in PrPC-deficient goats. These genes included a range of collagen-encoding genes, and proteases such as metalloproteinases (MMP1, MMP2, MMP14, ADAM15) and cathepsins. Several pro-inflammatory upstream regulators (TNF α, IL1 β, IFN γ) showed increased activation scores in goats devoid of PrPC. In conclusion, LPS challenge induced marked alterations in the lung tissue transcriptome that corresponded with histopathological and clinical findings in both genotypes. The increased activation of upstream inflammatory regulators and enrichment of ECM components could reflect increased inflammation in the absence of PrPC. Further studies are required to elucidate whether these alterations may affect the later reparative phase of acute lung injury.